Performance of Compressed Earth Brick with Sodium Silicate as Alkaline Activator - Zamri, Zafira Rozzetty; Burhanudin, Mohd Khairy (Recent Trends in Civil Engineering and Built Environment, 2024)
Nowadays, because of the country's development and expanding population, rapid construction has become the norm. Many building materials, including concrete and bricks are utilized in the construction of this structure. However, these rapid construction are causing a great harm towards the environment. There are a lot of pollution happening especially air pollution. Therefore, in order to prevent this phenomenon from getting worse, an alternative of compressed earth bricks (CEB) is used in constructions. CEB are a great alternative because it is eco-friendly. The manufacturing of CEB requires compression method unlike common burnt clay bricks. Regarding this matter, a study of using sodium silicate as alkaline activator in compressed brick is conducted. The main objectives of the study is to determine the physical and mechanical properties of the brick as well as determining the optimum content of the alkaline activator. The tests involve to determine the properties are density, water absorption and compressive strength tests. An approximate of 80 bricks with the size of 250mm x 125mm x 100mm will be produced for the tests. The ratio used for the brick mixture is 1:4:4 (Ordinary Portland Cement to Sand to Laterite soil) where 0%, 3%, 6%, 9% and 12% of sodium silicate will be used as alkaline activator. The results for each test are recorded for analysis in accordance to British Standard and ASTM. As for density test, the average results obtained ranges from 1900kg/m3 to 2000kg/m3 for both curing period. For water absorption, the ranges obtained for both curing periods are between 10% to 13%. Last but not least, for 7-days and 28-days curing period, only CEB with 0% sodium silicate (control variable) achieved more than 5N/mm2 compressive strength.